Notification mechanisms in second-screen scenarios: towards a balanced user experience - Almeida, Pedro Alexandre dos Santos (2016)
As technological devices surrounding the television are changing, so are viewers’ habits. When the interactive Television industry turns its focus to the development of second-screen applications, this paper reports on a study aiming to analyse the impact, on users, of notifications in second-screen scenarios. As part of the study, the research team developed a prototype that simulated an application able to deliver synchronized information related with TV content, notifying the user – through visual, audio and haptic stimuli - whenever new content was displayed in the tablet. The study included observation sessions, conducted in laboratory settings, with participants (N=12) being invited to watch a 15-minute film while using the application. Tests were conducted under a cognitive walk-through methodology, and data collected through direct observation and questionnaires. Results show that to achieve a balanced user experience in second-screen scenarios notifications on tablet should be combined with visual notifications on TV.